Pre-conditions of development of ideas about health and healthy way of life. - Shchekina N. B. (Kharkov National Pedagogical University, 2012)
Directions of development of ideas are examined about a health and healthy method of life on the basic stages of development of human civilization. The deposit of prominent philosophers, teachers, enlighteners in development of ideas of healthy method of life is analysed. It becomes firmly established that on the different stages of development of human society a problem of maintainance and strengthening of health and healthy way of life always were in the highlight of public and state figures. Characteristic for domestic pedagogics was attention to the problem of health from the side of teachers, psychologists, doctors. Directions of forming of health and healthy way of life are selected. The necessity of scientific researches is marked on perfection of methods, facilities and form of physical education.